PENERAPAN MODEL INQUIRY TERBIMBING DALAM PENINGKATAN MOTIVASI BELAJAR IPA TENTANG ENERGI DAN PERUBAHANNYA PADA SISWA KELAS V SD NEGERI KLEGENWONOSARI - Hidayah, Nurul; Suryandari, Kartika Chrysti; Ngatman, Ngatman (KALAM CENDEKIA PGSD KEBUMEN, 2017)
ABSTRACT Nurul Hidayah. THE USE OF GUIDED INQUIRY MODEL IN IMPROVING THE LEARNING MOTIVATION OF SCIENCE ON ENERGY AND THE CHANGING FOR FIFTH GRADE STUDENTS OF SD NEGERI KLEGENWONOSARI IN THE ACADEMIC YEAR OF 2016/2017. Thesis. Teacher Training and Education Faculty of Sebelas Maret University Surakarta. July 2017.The objectives of this study: (1) to describe the steps of applying learning Inquiry Guided model in improving learning motivation of IPA and (2) to improve student learning motivation through the application of guided inquiry model on science subjects for fifth grade students in even semester in SD Klegenwonosari in the academic year of 2016/2017.This study is a collaborative classroom action research (CAR) conducted in three cycles. Each cycle consists of two meetings and each meeting consists of planning, implementation, observation, and reflection. The subjects of this study are students of grade V SDN Klegenwonosari which amounted to 20 students. Sources of data in this study are, namely teachers, students, and documents. Data collection techniques used were questionnaires, observations, tests, interviews, and documentation. Data validity was using triangulation technique, ie triangulation of source and triangulation technique.The results of this study show: (1) the use of guided inquiry model is done through five steps, namely: (a) problem orientation, (b) conceptualization, (c) investigation, (d) conclusion, and (e) discussion. (2) the use of guided inquiry model can increase motivation and result in improvement of student learning outcomes. This is evidenced by the increase of students' learning motivation in every cycle. Average percentage in cycle I intrinsic motivation 65,75%, while extrinsic motivation 61,37%. Cycle II, intrinsic motivation 83,16%, extrinsic motivation 69,72%, and in cycle III, intrinsic motivation increase reach 90,17% and extrinsic motivation increase reach 79,10%. While the students' learning outcomes are evidenced by the improvement of learning outcomes, in the first cycle students who complete as much as 78.36%, on the second cycle as much as 90%, and in the third cycle as much as 97.5%.The conclusion of this research is the use of guided inquiry model can increase the learning motivation of IPA for fifth grade students of SDN Klegenwonosari in the academic year of 2016/2017.Keywords: Guided Inquiry Model, Energy and its changes, and Learning Motivation.